Michele Taruffo on common sense generalizations - Muffato, Nicola (2021)
A recurrent topic in Michele Taruffo’s work concerns the analysis and criticism of the notion of “common sense generalizations”. These are generalizations which constitute the implicit background and sometimes the explicit premises of all evidential and interpretive reasoning of legal operators and lay people, but they are also potentially dangerous when assumed without the due theoretical precautions. In this paper, I’ll reconstruct Taruffo’s point of view and conceptual distinctions about “common sense presumptions”, trying to enrich his framework with some commentaries, examples, and objections.